The Impact of Social Media and Browsing the Internet on English Learning in Higher Education, Setting At Lhokseumawe State Polytechnic (International Journal of Scientific Research and Management (IJSRM), 2024)
Cell phones have become an indispensable communication tool across the globe. With the technological advancements, cell phones have undergone a significant transformation from being stationary or boot telephones that required cables to hand-held devices that can be carried anywhere without cables. Today, smartphones have become increasingly sophisticated and offer features like cameras, internet access, email, and other applications that support human activities. Public places like airports, terminals, restaurants, or campus canteens are now equipped with WIFI or hotspots, making it easier for individuals to use the internet while enjoying food. However, the use of smartphones on campus is considered disruptive to the student education process. As a result, many higher education institutions prohibit the use of smartphones on their premises. In a recent research study, the authors examined the impact and effects of internet activities, such as browsing and social media usage, on improving students’ abilities, particularly in English. The study involved 80 students who completed a 30-question questionnaire. The data analysis revealed that almost all the students were active internet users, with 74 of them using smartphones for both browsing and social media. Only six students did not use smartphones for social media, indicating that Lhokseumawe State Polytechnic students rely heavily on the internet for their academic and personal needs. Out of the total respondents, 21 students spend 20 to 30 minutes a day on social media, accounting for 26.3 percent of the total. 19 students used smartphones for social media for about 2 to 4 hours. Surprisingly, 11 students were willing to spend more than 5 hours a day on social media. The findings reveal that most students at Lhokseumawe State Polytechnic are more inclined towards social media rather than browsing the internet. The t-test and F-test showed a significant correlation between browsing and social media usage with English achievement among students of Lhokseumawe State Polytechnic. It indicates that using the internet for browsing and social media has a positive impact on academic performance, particularly in English.